2020
DOI: 10.1021/acsami.0c17316
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Nanostructures Encapsulated with Metallic Nanodots for Smart SERS Sensing

Abstract: In virtue of uniform mesopores and core–shell nanoarchitectures, metallic nanodot-encapsulated hollow mesoporous nanostructures have shown promising potential in various applications. However, their fabrication with versatile tunability of the encapsulated metallic content has been a challenge. Herein, we have prepared metallic nanodot-encapsulated hollow mesoporous silica nanoparticles (M-HMSNPs) with adjustable inner metallic components. The sacrificial template of polystyrene (PS) nanoparticles precoated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It is found that the Raman spectra will be significantly enhanced if the sample is adsorbed on the surface of gold, silver, or copper. 46,47 As AuNPs affect the fluorescence signal and the Raman signal, AgNPs were chosen for fluorescence signal and Raman signal amplification. 48,49 Through experiments, we further confirmed that AgNPs have an enhancing effect on the Raman signal (Figure S4B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is found that the Raman spectra will be significantly enhanced if the sample is adsorbed on the surface of gold, silver, or copper. 46,47 As AuNPs affect the fluorescence signal and the Raman signal, AgNPs were chosen for fluorescence signal and Raman signal amplification. 48,49 Through experiments, we further confirmed that AgNPs have an enhancing effect on the Raman signal (Figure S4B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Their spontaneous motion can significantly enhance the mixing of various phases in solution, showing promising applications in detection and degradation of pollutants in water. [33][34][35][36][37][38] Joseph Wang et al reported an aptamer-modified graphene-based catalytic micromotors for an on-off fluorescence detection of ricin. 39 The movement of micromotors remarkably improved the fluorescence detection of ricin.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Currently, the SERS technique has been extensively applied in drug analysis, 6 virus detection, 7 , 8 food safety, 9 , 10 and biomedical sensors. 11 , 12 Usually, the efficiency of SERS signals is enormously derived from the geometric shape of metal nanostructures and their gap. Compared with the regular nanostructures (such as spheres), the shape can induce higher-density surface plasmons (SPs).…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS), a great enhancement effect of the local electromagnetic field caused by the collective oscillation of electrons in a conductive nanostructure (called the local surface plasmon resonance (LSPR)), has been proven to be an ultrasensitive technique to obtain highly specific Raman signals of targeting trace molecules. , Currently, the SERS technique has been extensively applied in drug analysis, virus detection, , food safety, , and biomedical sensors. , Usually, the efficiency of SERS signals is enormously derived from the geometric shape of metal nanostructures and their gap. Compared with the regular nanostructures (such as spheres), the shape can induce higher-density surface plasmons (SPs).…”
Section: Introductionmentioning
confidence: 99%